Entrepreneurship and territorial economic development in Algeria - Ferdj, Younes (Management and Entrepreneurship: Trends of Development, 2024)
Entrepreneurship and territorial economic development are two interdependent dimensions that play a crucial role in shaping the socio-economic dynamics of a region or country. Entrepreneurship, as a driver of innovation, job creation, and economic growth, is often closely linked to territorial economic development, where local prosperity is sought through specific strategies and actions. In the specific context of Algeria, entrepreneurship and economic development hold particular significance, given the unique challenges and opportunities facing the country. Entrepreneurial activity can not only energize local markets but also play a significant role in reducing unemployment, stimulating innovation, and building a robust economic foundation. Territorial economic development involves the implementation of policies and strategies to balance growth across different regions, promote the efficiency of local infrastructure, and enhance the quality of life for citizens. The complex interaction between entrepreneurship and economic development underscores the importance of understanding how these elements interact and mutually influence each other. This study will explore these dynamics specifically in the Algerian context, examining how entrepreneurship can be a crucial catalyst for territorial economic development and how, in turn, economic development can create an environment conducive to entrepreneurial growth. The problem addressed in this article is to study the key factors that have played a significant role in the dynamics of the entrepreneurial process. To address the question of the development paradigm of territories, we selected the region of Blida as a case study, as this province is located in the heart of the fertile agricultural plain of Mitidja, which has served as a springboard for the development of the agri-food industry. The statistical study relies on the results of a quantitative questionnaire survey conducted among a sample of agri-food companies, where the questions focus on the behaviors of entrepreneurs in territorial development. This work, in theory, follows an approach where the following theoretical concepts have served as explanatory, analytical, and interpretative elements of the survey data. Thus, the analytical exploitation of the survey data has allowed us to determine the characteristics and specificities of the entrepreneur as a creator-innovator according to J. Schumpeter (1912). JEL Classification: D21, L10, R10